Pengaruh Kontrak Pembiayaan Syariah terhadap Kinerja Profitabilitas Bank Mega Syariah - Nurhaliza, Vani; Yarmunida, Miti; Putry, Nurrahmah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
There are fluctuations between growth and decline in the distribution of Islamic financing, such as Murabahah, Mudharabah, and Musyarakah, which affect profitability performance as measured by ROA, ROE, and NOM during the 2022–2024 period. Inconsistencies were found in previous research findings regarding the effectiveness of each financing contract on Islamic banking profitability. This study aims to examine the extent to which Murabahah, Mudharabah, and Musyarakah financing affect the profitability of Bank Mega Syariah during the 2022–2024 period. A quantitative method was used, utilizing Bank Mega Syariah's quarterly financial report data as secondary data, which was then analyzed using multiple linear regression techniques. The results show that Murabahah and Mudharabah financing have not been able to optimally increase Bank Mega Syariah's profitability, especially in terms of operating margins. Musyarakah financing also does not show a significant effect on profitability. These findings indicate that increasing the volume of Islamic financing needs to be balanced with effective risk management and operational efficiency to positively contribute to the bank's financial performance.